Pengetahuan dengan Peran Orangtua dalam Penggunaan Gadget pada Anak Usia 6-8 Tahun - Ishariani, Linda; Muhammad Taukhid; Khoirunnisa Nur Aprilia (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
The use of gadgets in technological development is widely used, especially by children because they have interesting features. Excessive use of gadgets can have a negative impact on children's development and thinking patterns. Efforts can be made to increase parents' knowledge and participation in controlling children's gadget use. The research aims to determine the relationship between knowledge and the role of the family in using gadgets in children aged 6-8 years. Correlation research design with a cross-sectional approach. The population is 120 respondents, the sample is 26 parents who have children aged 6-8 years. The instrument used was a questionnaire. Data analysis with Spearman Rank. The results of research on family knowledge about gadgets showed that almost all respondents (88.5%), namely 23 respondents had a good level of knowledge, while the majority of respondents (61.5%) namely 16 people had a good role with a p-value of 0.019 at the level of error < 0.05 means there is a relationship between knowledge and the role of the family in using gadgets in children aged 6-8 years. The direction of the strength of the relationship is positive in the sufficient category (r = 0.457) meaning that the better the parents' knowledge regarding gadgets, the better the role of the family. in using gadgets to be good. Increasing knowledge is accompanied by the role of parents through educating health workers regarding monitoring the use of gadgets so that it can influence children's development for the better. It is recommended for parents to control and manage the maximum time their children use gadget